The Role of Community Empowerment in the Development of a Marketing Communication Strategy for Kembang Kuning Tourism Village - Purworini, Dian; Chasana, Rona R. B.; Palupi, Palupi; Setyawan, Sidiq; Triyono, Agus; Yuwono, Iswahyudi T. (UI Scholars Hub, 2023)
This study examines initiatives intended to enhance community empowerment in the tourism village of Kembang Kuning, Central Java, Indonesia. One problem facing this community is an inability to carry out effective promotion to realize the tourism potential of the village. Despite the Kembang Kuning village’s potential qualities for tourism, there is a lack of local knowledge about marketing and communication strategies. The lack has hindered efforts to make the village known nationally. This study seeks to raise awareness and understanding of promotion strategies and simultaneously develop marketing communication strategies through active participation by the village tourism management team. Qualitative methods were employed in this study, and information was gathered through field observations, interviews, documentation, and active participation. This study found that in Kembang Kuning tourism village, community empowerment and tourism development when combined with a promotion and marketing communication strategy, have the potential to increase the village’s tourism potential.